2014
DOI: 10.1055/s-0034-1376870
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Fat-Graft: A Simple Tool for Reconstruction of Small Deep Defects of the Nose

Abstract: Small deep defects of the nose after resection of benign or malignant skin tumors are a common challenge in facial plastic surgery daily routine. The use of local flaps has several disadvantages for what reason they are a minor or no option especially in certain localizations in the lower third of the nose. Many elder patients suffer from comorbidities where complex more-staged reconstructional procedures drop out. We present a technique of nasal defect closure with a skin-fat composite graft. Between April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Deep defects of the nasal alae present reconstructive challenges due to complex anatomic topography, nearby free margins, and minimal elasticity of nearby thick sebaceous skin. The use of traditional fullthickness skin grafts for lower nose reconstruction has been described, but recommendations are typically limited to shallow and small defects <1 cm [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep defects of the nasal alae present reconstructive challenges due to complex anatomic topography, nearby free margins, and minimal elasticity of nearby thick sebaceous skin. The use of traditional fullthickness skin grafts for lower nose reconstruction has been described, but recommendations are typically limited to shallow and small defects <1 cm [3].…”
Section: Discussionmentioning
confidence: 99%
“…While traditional teaching endorses defatting FTSGs, several studies have demonstrated that the inclusion of subcutaneous fat may reliably restore contour without significantly affecting graft survival [3,4]. We introduce the concept of sculpting the graft into a boat-shaped or "navicular" form, which allows for sufficient volume restoration and good cosmesis while avoiding more extensive surgical repairs of the nasal ala.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have challenged this principle by using skin grafts leaving the fat attached, thus allowing the ability to adjust the thickness of the graft to fill the defect [23]. Kreutzer, von Gregory and Fischer recently reviewed their results using “skin-fat-grafts” for small deep defects of the nose [24]. Their case series demonstrates 46 grafts used to reconstruct defects with a median area of 83 mm 2 .…”
Section: Cutaneous Reconstructionmentioning
confidence: 99%
“…Skin lesions can be caused by many factors such as accidents, diabetic complications, burns, or superficial surgery [ 1 ]. Autogenous skin transplantation, or biopolymers used for fabrication of the artificial skin, represents the most common approach used for wound closure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%